The Mexican Value-Added Tax (VAT) : Characteristics, Evolution, and Methodology for Calculating the Base - Aguirre, Carlos (IMF Working Papers; Working Paper ;, 1987)
The value-added tax (VAT) is often a major component of national fiscal structures. While its effects on allocative efficiency, inflation, income distribution, and tax administration have been addressed, little work, exists on the theoretical base of a VAT, given its structure. This is essential for knowing how much of the base is actually taxed. Using Mexican national accounts and input-output tables, this paper develops a methodology for calculating the theoretical base of the Mexican VAT for 1980 and 1983 (two years whose individual VAT structures were considerably different). The method is applicable to other VAT systems as well.